Види та методи тестування інтерфейсу, як інструмент забезпечення якості продукту - Ківва, В. О. (ХНУРЕ, 2021)
Interface testing is one of the most important stages of a product development lifecycle. It provides quality, relevance, uninterrupted operation in the future, high performance of application components and successful interaction with other applications. The main purpose of interface testing is to identify errors of the following nature: errors in the func tionality of the interface and the absence or errors in the design of the interface.
Keywords: тестування якості продукту; тестування інтерфейсу